Student Writen Conversation In The Midst Of Social Media Era - Eko Kuntarto (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2020)
This research aimed to explain the model of writen conversationin the social media era, such presence of WhatsApp (WA) as well as to explore some of the positive contributions of WA used in building the Real Life Communication. By applying the Exploratory design, this research involved 4 participants as a purposively selected data source with indicators as WA users. Data were collected through Focus Group Discussion, Interview, and Observation and analyzed by several stages i.e. data reduction, displaying data, categorizing, and verifying and concluding. The results showed that Indonesia writen conversationcan decrease as the dominant use of WA was not wise. Nevertheless, the use of WA applications also had some positive contributions in building a real relationship. Finally, the assumption that the negative impact of using the WA application should be able to change the mindset and positive attitude in initiating and defending an oral interaction.